Thematic Tourism Development Model In Tista Tourism Village, Tabanan Regency - Ni Desak Made Sukma Dewi; Ni Made Sofia Wijaya; Agus Muriawan Putra (International Journal of Technology and Education Research, 2025)
This study aims to analyze a thematic tourism development model that reflects the unique identity of Tista Tourism Village, Tabanan Regency. This area is a rural-based tourism destination that relies on natural, agricultural, and local cultural potential, with high tourist interest in the community's daily activities. The increase in similar tourism villages in the surrounding area demands the creation of tourism products that can provide more authentic and memorable experiences while sustainably preserving the village's culture, environment, and identity. This effort is also expected to facilitate the creation of tourism products that can meet market demands and expectations, support the sustainability of village identity, and fulfill the aspirations of the community and village government. The research method uses a qualitative descriptive approach with data collection techniques through observation, structured interviews, documentation, and literature studies to analyze existing conditions and identify internal and external factors as a basis for formulating village themes. Informants were selected purposive from government, management, community, and tourist elements. Data analysis was conducted through a process of reduction, systematic presentation, and drawing conclusions, reinforced by a SWOT analysis to map the strengths, weaknesses, opportunities, and threats that influence model development. The results of the study show that Tista Village is at the development stage in the TALC (Tourism Area Life Cycle), with spontaneous and interactive community participation. The theme “CANDA TAWA” (Culture, Adventure, Nature, Daily Activity, Agriculture, Tradition, Authenticity, Wellness, Arts and Craft) is formulated as a thematic tourism theme, which becomes a reference for developing local identity-based tourism to strengthen the competitiveness of destinations adaptively.